2002
DOI: 10.1124/jpet.301.3.1060
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of TP and EP3 Receptors in Vasoconstrictor Responses to Isoprostanes in Pulmonary Vasculature

Abstract: Although isoprostanes generally act on smooth muscle via TXA 2 -selective prostanoid receptors (TPs), some suggest other prostanoid receptors or possibly even a novel isoprostaneselective receptor might be involved. We studied contractions to several isoprostanes in porcine pulmonary vasculature using organ bath techniques. 8-iso-prostaglandin E 2 (PGE 2 ) was the most potent and efficacious of the isoprostanes, with a log EC 50 of Ϫ7.0 Ϯ 0.2 in the pulmonary artery and Ϫ6.8 Ϯ 0.2 in the pulmonary vein. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 28 publications
(42 reference statements)
0
53
0
1
Order By: Relevance
“…In addition, Belik et al (9) have shown that the 1-wk-old rat pulmonary vascular response to 8-iso-PGF2␣ is clearly distinct from the adult. This age-dependent difference in force development was similar to the pattern previously described during stimulation of rat pulmonary artery with other agonists, including the TxA 2 analog U46619, which appears to act via the same receptor as 8-iso-PGF 2␣ (9,21). No study has characterized the response to isoprostanes in neonatal systemic vessels.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In addition, Belik et al (9) have shown that the 1-wk-old rat pulmonary vascular response to 8-iso-PGF2␣ is clearly distinct from the adult. This age-dependent difference in force development was similar to the pattern previously described during stimulation of rat pulmonary artery with other agonists, including the TxA 2 analog U46619, which appears to act via the same receptor as 8-iso-PGF 2␣ (9,21). No study has characterized the response to isoprostanes in neonatal systemic vessels.…”
mentioning
confidence: 51%
“…Another point of interest is that some of the F-ring isoprostanes, such as 8-iso-PGF 2␣ and 8-iso-PGF 2␤ , produced, in our experiments, levels of contraction that are comparable with those induced by the E-ring isoprostanes. In contrast, in the porcine adult pulmonary vessels, F-ring isoprostanes induced markedly weaker contractions than E-ring isoprostanes (21,26). Finally, Janssen and Tazzeo (21) observed that, although the contractions induced in adult porcine PA and PV by 8-iso-PGE 1 , 8-iso-PGF 1␣ , 8-iso-PGF 2␣ , and 8-iso-PGF 2␤ were essentially completely prevented by TP receptor blockade, 8-iso-PGE 2 was able to evoke substantial contraction of PV in the maintained presence of TP receptor blockade.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many have described contractile responses to isoprostanes in a wide variety of arterial beds, generally via stimulation of thromboxane A 2 receptors (TP receptors), which then enhance the Ca 2ϩ -sensitivity of the contractile apparatus through some mechanism that is largely dependent on tyrosine kinase activation (Janssen, 2001). They may also cause vasoconstriction through an action on PGE 2 -selective (EP) receptors coupled to release of internally sequestered Ca 2ϩ (Janssen and Tazzeo, 2002). More recently, some have identified important vasodilatory actions of isoprostanes (Jourdan et al, 1997;Janssen et al, 2000;Janssen et al, 2001); however, the signaling mechanisms underlying those inhibitory responses have not been investigated.…”
mentioning
confidence: 99%
“…Alguns isoprostanos possuem propriedades vasoconstritoras (JANSSEN et al, 2001;JANSSEN, TAZZEO, 2002;YI et al, 2006), enquanto outros são vasodilatadores ZHANG et al, 2005 (WEI et al, 1996). Ao ativar canais para potássio, agentes oxidantes promovem hiperpolarização e fechamento de canais para cálcio dependentes de voltagem, resultando na diminuição do influxo de cálcio (SCHACH et al, 2007).…”
Section: Discussão -101unclassified